FENOMENA DESAIN BATIK SURAKARTA DAN YOGYAKARTA - Pujiyanto Pujiyanto (Gelar : Jurnal Seni Budaya, 2013)
Batik Surakarta and Yogyakarta has their own peculiarities in comparison with batik from otherregions. Batik Surakarta particular distinctiveness lies in the color batik background leads to ayellow wish brown. (soga genes,soga wonogiren and soga Java) while Batik Yogyakarta has aclean white background with white fabric fringe. The batik lovers of ancients times did not justcreate something beautiful to look at, but also gives meaning which are closely related to thephilosophy of life. They are created accordance with the motif of the message and hope thatsincere and noble. So that can bring good and happiness to the wearer. The use of decorativemotif often associated with the symbol as well as the overall shape of ornaments planned with aspecific purpose, such as esteem, welfare or wealthy. There is different between past and currentcondition that is influenced by contemporary circumstances. Change and shift of batik Surakartaand Yogyakarta are caused by various things such as aesthetic, technology, economy, social,cultural and political.